2009
DOI: 10.1111/j.1365-2982.2008.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability in antroduodenal manometry

Abstract: Interobserver variability affects investigations involving assessment of complex visual data, such as histopathology, radiology and motility. This study assessed interobserver variation for interpretation of antroduodenal manometry (ADM), as this has not been previously investigated. Thirty-five ADM recordings from children aged 0.3-18 years were independently evaluated by five experienced paediatric gastroenterologists who were blinded to cases' clinical histories. Intra-class correlation (ICC) was analysed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…In the present study, observer 2 showed 60% agreement regarding GCR and overall study interpretation, suggesting the main cause for suboptimal overall study interpretation was variability in interpreting the GCR instead of the manner in which the data were displayed. Problems in evaluating the meal response on bowel motility are not limited to the colon manometry; Connor et al reported a greater variability in evaluating postprandial hypomotility for antroduodenal manometry testing in children (12). Although the kappa statistic is commonly used to assess reliability, caution is required when interpreting the magnitude of the kappa statistic because it is influenced by the prevalence of the rating (if the prevalence is high, chance agreement is also high and kappa is reduced accordingly) and by the bias (when there is a large bias, kappa is higher).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, observer 2 showed 60% agreement regarding GCR and overall study interpretation, suggesting the main cause for suboptimal overall study interpretation was variability in interpreting the GCR instead of the manner in which the data were displayed. Problems in evaluating the meal response on bowel motility are not limited to the colon manometry; Connor et al reported a greater variability in evaluating postprandial hypomotility for antroduodenal manometry testing in children (12). Although the kappa statistic is commonly used to assess reliability, caution is required when interpreting the magnitude of the kappa statistic because it is influenced by the prevalence of the rating (if the prevalence is high, chance agreement is also high and kappa is reduced accordingly) and by the bias (when there is a large bias, kappa is higher).…”
Section: Discussionmentioning
confidence: 98%
“…Typically, acid suppression is continued unless the patient is more likely to experience symptoms during testing off therapy thus providing greater insight into the pathophysiology of symptoms. 6,7,11,13 While other medications may have an effect on motility (e.g baclofen, antipsychotic medications, attention deficit medications), stopping them prior to testing may not medically feasible. Similarly, while vagal nerve stimulators may have an impact on esophageal motility, the risk/benefit analysis for turning off the stimulator must be considered.…”
Section: Indications For Antroduodenal Manometrymentioning
confidence: 99%
“…It has contributed to the understanding of the pathophysiology of neuromuscular disorders of the stomach and small bowel by assessing pressure amplitude and coordination. 6,7,10,11 In most institutions, ADM is still performed using traditional perfused catheters (Figures 2 and 3) though high resolution catheters are now available (Figures 2 and 3). 8…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-observer agreement for normal vs abnormal antroduodenal motility compares well with other diagnostic tests, and specific patterns may suggest disease in both children and adults. 11 Clinical indications include diagnostic clarification of slow gastric or small bowel transit (neuropathy or myopathy), unexplained abdominal pain, and nausea/vomiting. 12 Pitfalls include confounding by cough or movement, displacement of the catheter in the antrum/duodenum, and common manometric features among several dysmotility syndromes.…”
Section: Antroduodenal Manometrymentioning
confidence: 99%